Lactobacillus delbrueckii subsp. bulgaricus KLDS 1.0207 Exerts Antimicrobial and Cytotoxic Effects in vitro and Improves Blood Biochemical Parameters in vivo Against Notable Foodborne Pathogens - Evivie, Smith Etareri; Abdelazez, Amro; Li, Bailiang; Lu, Shijia; Liu, Fei; Huo, Guicheng (Frontiers in Microbiology, 2020)
Globally, foodborne diseases (FBDs) result in millions of sicknesses and deaths annually. Cumulative evidence suggests that the use of probiotic lactic acid bacteria (LAB) strains could be a viable alternative in inhibiting the activities of foodborne pathogens. This study aims to evaluate the in vitro antimicrobial, cytotoxic, and tolerance levels of Lactobacillus bulgaricus KLDS 1.0207 against two notable foodborne pathogens – Escherichia coli ATCC25922 and Staphylococcus aureus ATCC25923. Afterward, a 48 BALB/c mice-trial was used to assess its ameliorative effects on weight and serum biochemical parameters. Results showed that the cell-free supernatant (CFS) of this strain significantly inhibited both pathogens, but these effects were abolished at pH 6.5 and 7.0 (P<0.05). Also, 6.96±0.02 log CFU mL-1 of L. bulgaricus KLDS 1.0207 was still viable after three hours in simulated gastric juice and at pH 3.0, indicating that this strain was a potential probiotic candidate. Also, inflammatory activities in RAW264.7 cells were significantly inhibited using 109 CFU mL-1 of L. bulgaricus KLDS 1.0207 cells (P<0.05). Significant weight losses were also prevented in the TLBSA (from 19.42±1.04 to 19.55±0.55 g) and TLBEC (from 22.86±0.90 to 14.77±9.86 g) groups compared to their respective model groups (TSA – from 21.65±1.80 to 20.14±1.84, and TEC – from 21.45±0.82 to 14.45±9.70 g). Besides, there was a slight weight gain in the S. aureus prevention group (TLBSA) compared to the model group (TSA). Serum biochemical analyses revealed that the total cholesterol (TC), triglycerides (TG), low-density lipoprotein (LDL), and some mineral levels were markedly increased by S. aureus and E. coli administrations but were reversed to normalcy in both prevention groups (TLBSA and TLBEC). Interestingly, high-density lipoprotein (HDL) levels, which were initially disrupted in the model groups, were restored in the prevention groups (TLBSA and TLBEC). This study presents L. bulgaricus KLDS 1.0207 as a promising probiotic candidate with antimicrobial, anti-inflammatory, acid, and bile tolerant and lipid-regulating applications. It also gives valuable insights for targeted future in vivo treatment and prevention studies involving other probiotic LAB candidates. Future in vivo studies elucidating specific mechanisms behind the in vitro antimicrobial, cytotoxic, and in vivo ameliorative effects are warranted.